Myiasis in female external genitalia - Kataria, Usha (Medknow Publications & Media Pvt Ltd, 2013)
Myiasis is derived from the Greek word-“Myia”, meaning “fly”. The term was first introduced by Hope in 1840 and refers to the infestation of human beings with dipterous larvae (maggots). Presence of maggots on exposed parts is already known, but on covered parts like external genitalia it is very rare. We hereby describe a case of young unmarried female who presented with multiple sinuses over external genitalia along with maggots coming out of it.